Combined evaluation of myocardial perfusion and coronary morphology in the identification of subclinical CAD - Vincenti, G.; Quercioli, A.; Zaidi, H.; Nkoulou, R.; Dewarrat, S.; Rager, O.; Ambrosio, G.; Seimbille, Y.; Mach, F.; Ratib, O.; Schindler, T. H. (Nuklearmedizin - NuclearMedicine, 2010)
Purpose: To evaluate the mean effective radiation dose of 13N-ammonia PET/CT and ECGpulsing CT angiography (CTA) in the evaluation of myocardial perfusion, myocardial blood flow (MBF) and coronary morphology for the identification of subclinical CAD. Patients, material, methods: Following rest-stress 13N-ammonia PET/CT perfusion imaging and MBF quantification, ECG-pulsing CTA at a pulse window of 70% of the R-R cycle was performed in ten healthy controls and in sixteen individuals with cardiovascular risk factors. Individual radiation dose exposure for ECG-pulsing CTA was estimated from the dose-length product. Results: PET demonstrated normal perfusion in all study individuals, while hyperemic MBFs during dipyridamole stimulation and the myocardial flow reserve (MFR) in cardiovascular risk individuals were significantly lower than in healthy controls (1.34 ± 0.26 vs. 2.28 ± 0.47 ml/g/min and 1.48 ± 0.39 vs. 3.24 ± 0.81, both p . 0.0001). Further, ECG-pulsing CTA identified mild calcified and non-calcified coronary plaque burden in 7 (43%) individuals of the cardiovascular risk group. Rest-stress 13N-ammonia PET/CT perfusion study yielded a mean effective radiation dose of 3.07 ± 0.06 mSv (2.07 ± 0.06 mSv from the rest-stress 13N-ammonia injections and 1.0 mSv from the 2 CT transmission scans), while ECG-pulsing CTA was associated with 5.57 ± 2.00 mSv. The mean effective radiation dose of the combined 13N-ammonia PET/CT and ECG-pulsing CTA exams in the evaluation of myocardial perfusion and coronary morphology was 8.0 ± 1.5 mSv. Conclusion:13N-ammonia PET/CT and ECG-pulsing CTA affords cardiac hybrid imaging studies in the evaluation of subclinical CAD with a relatively low mean effective radiation exposure of 8.0 ± 1.5mSv.
Keywords: Low dose; computed tomography coronary angiography; coronary circulation; feasibility; myocardial blood flow; retrospective gating; positron emission tomography